SISTEM PERINGATAN DINI IBU HAMIL YANG AKAN MELAKUKAN PERSALINAN (Information Technology and Telematics, 2013)
Early Warning System is a system of biological or other techniques used by an individual or group to inform future hazards. In this case, including an early warning system for civilian purposes. According to the Household Health Survey (Household Health Survey) in 2001, the direct cause of nearly 90 percent of maternal deaths occur during delivery and immediately after delivery. the purpose of this research is to design and develop an early warning system of pregnant women who will perform labor. Keywords : Warning System, Maternity.